1991
DOI: 10.1071/bt9910161
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Strains of Fusarium oxysporum f.sp. cubense by Production of Volatiles

Abstract: The production of volatiles on steamed rice by Australian isolates of Fusarium oxysporum f. sp. cubense correlated well with race and vegetative compatibility group (VCG). All race 4 isolates (VCGs 0120, 0129) produced distinctive volatile odours which gave characteristic gas chromatograms where the num- ber of peaks equated to VCG. Race 1 (VCGs 0124, 0125) and race 2 (VCG 0128) isolates, as well as non-pathogenic isolates of F. oxysporum from the banana rhizosphere, did not produce detectable volatiles and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 0 publications
2
26
0
1
Order By: Relevance
“…These include vegetative compatibility (Buxton, 1962;Puhalla, 1985), pathogenicity on different crops (Brake et al, 1990;Pegg et al, 1993;Pegg et al, 1994;Ploetz, 1994;Su et al, 1986;Waite and Stover, 1960), isozyme profiling (Ploetz, 1990), volatile compound production (Moore et al, 1991), and chromosome number and genome size (Boehm et al, 1994). A major disadvantage of these characters is their limited variation and that some, such as pathogenicity, are under strong selection pressure.…”
Section: The Evolution Of Fusarium Oxysporummentioning
confidence: 99%
“…These include vegetative compatibility (Buxton, 1962;Puhalla, 1985), pathogenicity on different crops (Brake et al, 1990;Pegg et al, 1993;Pegg et al, 1994;Ploetz, 1994;Su et al, 1986;Waite and Stover, 1960), isozyme profiling (Ploetz, 1990), volatile compound production (Moore et al, 1991), and chromosome number and genome size (Boehm et al, 1994). A major disadvantage of these characters is their limited variation and that some, such as pathogenicity, are under strong selection pressure.…”
Section: The Evolution Of Fusarium Oxysporummentioning
confidence: 99%
“…Each segment was cut into 5 subsections prior to plating onto 1/6 PDA amended with 0.5 g/L of streptomycin, and incubated at 20°C under a black light. The volatile odour test (Moore et al 1991) was used to distinguish between saprophytic and pathogenic strains of Fo. Five mycelial replicates taken from each monoconidial pure culture were tested.…”
Section: Soil and Soil Treatment Preparationmentioning
confidence: 99%
“…Stover (1962) showed that isolates from Bluggoe, which were placed in race 2, did not produce an odour, whereas isolates in race 1 belonged to either odoratum or inodoratum. However, Moore et al (1991) showed that the production of volatiles on steamed rice by Australian isolates of F. oxysporum f. sp. cubense correlated well with common vegetative compatibility groups of race 4 isolates.…”
mentioning
confidence: 99%
“…cubense were cultured on steamed rice (25 mL of rice and 50 mL of water added into 100 mL Erlenmeyer flasks, which were plugged with cotton-wool and sterilized by autoclaving at 121 o C for 20 minutes). Cultures were grown at 28 o C. After 10 days, cultures were classified based upon the presence of a strong volatile odor (Moore et al, 1991). From the 46 isolates of F. oxysporum f. sp.…”
mentioning
confidence: 99%